Association of nutrient supplement use in older adults with chronic diseases: a cross-sectional study - Tian, Hua; Chen, Jie (Frontiers in Nutrition, 2026)
IntroductionWith advancing age, physiological and social changes increase the risk of malnutrition among older adults. Dietary supplements are a prevalent strategy for maintaining nutritional balance, enhancing health, and preventing chronic diseases.MethodsThis study analyzed data from 9,986 participants aged 65 and older, drawn from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS), to compare supplement users and non-users. The data were analyzed using Mann–Whitney U test and Chi-square test.ResultsThe results revealed that only 11.91% older participants used nutrient supplements, and Calcium was the most used nutrient supplements. The typical user was women without spouses living with family, reporting a moderate lifestyle, high life satisfaction, and good health. There were potential associations between nutrient supplement use with chronic diseases, e.g., hypertension, heart disease, stroke and cerebrovascular disease, diabetes, and pneumonia or bronchitis.ConclusionThese findings suggest that nutrient supplement strategies should be personalized based on an individual’s chronic diseases. This research provides a crucial evidence base for health professionals to develop targeted interventions aimed at preventing the onset and deterioration of common chronic diseases in older adults.